Growth and production of crisp lettuce (Lactuca sativa L.) using different doses of nitrogen and magnesium - Preciado-Mongui, Ingrid Marcela; Reyes-Medina, Andrea Johana; Romero-Barrera, Yajaira; Álvarez-Herrera, Javier G.; Jaime-Guerrero, Marilcen (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Lettuce is part of the group of leafy vegetables that sees high consumption worldwide. However, population increases have forced excessive increases in fertilization, raising N levels both in the water and the soil and leading to serious environmental problems. As a result, appropriate fertilization management must be carried out; therefore, this study aimed to determine the effect of nitrogen and magnesium on the growth and yield of crisp lettuce. A randomized complete block design was carried out with 10 treatments: a control plus nine treatments with a central compound and different combinations of nitrogen and magnesium doses. The variables leaf area ratio, SPAD chlorophyll index and relative growth rate decreased throughout the crop cycle. The application of 150 kg ha-1 of N + 18 kg ha-1 of Mg generated the highest production values and net assimilation rate. The response surface graph yielded a model with a maximum yield of 21 t ha-1 using fertilization with 93.8 kg ha-1 of nitrogen and 12.4 kg ha-1 of magnesium. The lower doses of both nitrogenous and magnesium fertilization showed the highest values of agronomic efficiency and partial productivity.